DEVELOPMENT OF GUIDED INQUIRY BASED WORKSHEETS BIOSORPSION OF IRON METAL IN WELL WATER USING PAPER WASTE WITH MODIFICATION OF CITRIC ACID - Ade Sulaeman; Cucu Zenab Subarkah; Yulia Sukmawardani (Gunung Djati Conference Series, 2021)
The purpose of this study to describe the view worksheet based guided inquiry, and analyze the results of the validation test worksheet based guided inquiry Fe metal biosorption in well water using citric acid modified paper waste. The method used in this research is Design Based Research (DBR) using the ADDIE development design (analysis, design, development, implementation, and evaluation) which is done up to Development stage. The instruments used were worksheet grids, worksheets, and validation test filled out by three expert validators. The result of worksheet validation test is that the mean count is 0.80, the highest count being 0.916 and the lowest count being 0.75. Guided inquiry based worksheets are declared valid and ready to be used to support the learning process.